Introduction to food, feed, and health wealth in African yam bean, a locked-in African indigenous tuberous legume - Adewale, Babasola Daniel; Nnamani, Catherine Veronica (Frontiers in Sustainable Food Systems, 2022)
The African yam bean, Sphenostylis stenocarpa Hochst Ex. A. Richmond, Harms, is an indigenous tuberous legume of the humid tropics of Africa. Its edible pulse and tuber host significant promises for food, nutrition, and health security. It was identified as a counterpart of cowpea in the 1970s and rated to be highly nutritious, but notable constraints have denied it research and funding attention. “Cowpea revolution” further deprived focus on the African yam bean. However, some research updated and promoted its significant food, feed, and nutritional-pharmaceutical values between 1973 and 2000. The global trend for food diversification has further improved awareness and research on the African yam bean this past decade, but research focus on the tuber is incomparably small. The abundant minerals, vitamins, and bioactive compounds in the two economic products unveiled in the present review assure food, health, and nutritional security. The analytical comparison of nutritional values of the African yam beans and other grain legumes demonstrated the significant place of the crop among its counterparts. Furthermore, investigative research identified the grain as a good substitute for soybean for livestock feed formulations. Although no clinical study has been reported, some in vivo, in vitro, and ex vivo biological activities and human studies of the two economic products revealed their efficacy in the management of anti-natal lactation induction, anemia, diabetes, arthritis, etc. However, African yam bean still suffer displacement in rank, utilization, and popularity compared to the “favored” legumes. While the present review adds to its advocacy, awareness, and utilization, a coordinated research program that will boost its value chain is most necessary for progress.